ADDITION IN THE TRANSLATION OF JAMES DASHNER’S THE SCORCH TRIALS INTO INDONESIAN MEIDYNA ARRISANDI’S THE SCORCH TRIALS - Maisyarah, Rizki (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2019)
Addition is one of translation strategies in Structural Shift that is aimed to maintain the original meaning from source language into target language. This research studied about Addition in the translation of James Dashner’s The Scorch Trials into Indonesian Meydina Arrisandi’s The Scorch Trials. The Scorch Trials novel was chosen because the Addition frequently found in its translation version. Addition is determined based on the explicit structure found in the target language and it is being analysed using componential analysis and propositional analysis through semantics viewpoint. Additionally, through pragmatics viewpoint, implicature, context analysis, and deixis analysis through are used in the analysis. There are 124 data found from the novel; and from those data, 1datum is full equivalent, 1 datum is partial equivalent, and 1 datum is no equivalent presented in the paper as representation.. This research is aimed to identify how addition is used in the translation process, and it was found that addition is especially used to make clear the implicit meaning from the source language or to maintain the similar meaning.